Emergency Provider Use of Plain Radiographs in the Evaluation of Pediatric Constipation. Issue 9 (September 2019) - Kearney, Ryan; Edwards, Todd; Bradford, Miranda; Klein, Eileen
Abstract : Background: More than half of children evaluated as outpatients for abdominal pain are diagnosed with constipation. X-ray use in this scenario is variable: less than 5% in clinic settings, greater than 70% in emergency departments. X-rays increase misdiagnosis rate, remain costly, and involve radiation exposure. Objectives: The aim of this study was to assess the use of plain radiographs by pediatric emergency medicine (PEM) providers in the diagnostic evaluation and management of pediatric constipation. Methods: A cross-sectional survey of PEM providers was performed. Survey participants were subscribers to the American Academy of Pediatrics Section on Emergency Medicine Listserv. To assess diagnostic and therapeutic approaches, participants were presented a case of pediatric constipation meeting Rome III clinical criteria. Participants also categorized frequency of x-ray use, reasons for obtaining, estimated diagnostic utility, and elements of institutional standard approach. Descriptive statistical analyses were performed. Results: Three hundred five of 1272 Listserv members (24%) responded. Ninety-nine percent elected to treat for constipation in a case meeting Rome III clinical criteria; one third (31%) would obtain plain radiographs for this same scenario. Plain radiographs were viewed as somewhat (59%) or minimally (29%) value-added in the evaluation of suspected pediatric constipation. Obtaining family buy-in (44%) was the most common reason for utilizing plain radiographs. Frequency of use varied across geographic regions and with participant and hospital characteristics. Conclusions: This survey suggests that many PEM providers obtain radiographs to convince families of the diagnosis of constipation. This is not a viable management plan given the risks of radiation as well as costs. There remains room for improvement as we attempt to reduce use of radiation in the evaluation of common pediatric illnesses.